Integrating Radiologic and Clinical Features to Predict VSX1 Expression in Clear Cell Renal Cell Carcinoma - Federico Greco; Andrea Panunzio; Daniele Sergi; Marco Cataldo; Caterina Bernetti; Alessandro Tafuri; Bruno Beomonte Zobel; Carlo Augusto Mallio (Current Oncology)
Radiogenomics explores the connection between medical imaging features and underlying genetic profiles [...]